Temporal change in minimum mortality temperature under changing climate: A multicountry multicommunity observational study spanning 1986-2015 - Yang, Daewon; Hashizume, Masahiro; Tobías, Aurelio; Honda, Yasushi; Roye, Dominic; Oh, Jaemin; Dang, Tran Ngoc; Kim, Yoonhee; Abrutzky, Rosana; Guo, Yuming; Tong, Shilu; Coelho, Micheline de Sousa Zanotti Stagliorio; et al. (Environmental epidemiology (Philadelphia, Pa.), 2024)
BACKGROUND: The minimum mortality temperature (MMT) or MMT percentile (MMTP) is an indicator of population susceptibility to nonoptimum temperatures. MMT and MMTP change over time; however, the changing directions show region-wide heterogeneity. We examined the heterogeneity of temporal changes in MMT and MMTP across multiple communities and in multiple countries. METHODS: Daily time-series data for mortality and ambient mean temperature for 699 communities in 34 countries spanning 1986-2015 were analyzed using a two-stage meta-analysis. First, a quasi-Poisson regression was employed to estimate MMT and MMTP for each community during the designated subperiods. Second, we pooled the community-specific temporally varying estimates using mixed-effects meta-regressions to examine temporal changes in MMT and MMTP in the entire study population, as well as by climate zone, geographical region, and country. RESULTS: Temporal increases in MMT and MMTP from 19.5 °C (17.9, 21.1) to 20.3 °C (18.5, 22.0) and from the 74.5 (68.3, 80.6) to 75.0 (71.0, 78.9) percentiles in the entire population were found, respectively. Temporal change was significantly heterogeneous across geographical regions (P < 0.001). Temporal increases in MMT were observed in East Asia (linear slope [LS] = 0.91, P = 0.02) and South-East Asia (LS = 0.62, P = 0.05), whereas a temporal decrease in MMT was observed in South Europe (LS = -0.46, P = 0.05). MMTP decreased temporally in North Europe (LS = -3.45, P = 0.02) and South Europe (LS = -2.86, P = 0.05). CONCLUSIONS: The temporal change in MMT or MMTP was largely heterogeneous. Population susceptibility in terms of optimum temperature may have changed under a warming climate, albeit with large region-dependent variations.
Keywords: Human adaptation; Temporal change; Heterogeneity; Climate change; Minimum mortality temperature